EFL Students’ Attitudes toward the Use of Meta AI on WhatsApp in Writing at Vocational High School - Salsabila Jaya Masito; Syifa’ Khuriyatuz Zahro; Irmayani Irmayani (Explorations in English Learning, 2026)
This study explores the attitudes of EFL students toward the use of Meta AI on WhatsApp in Writing at a vocational high school. Given the increasing prevalence of artificial intelligence in educational settings, many students have begun utilizing AI tools to support their writing activities. This research specifically focuses on Meta AI, an AI integrated within the widely used WhatsApp application, analyzing student attitudes from three dimensions: cognitive, affective, and behavioral. Additionally, the study examines the benefits and challenges experienced by students when using this AI-assisted writing tool. A qualitative descriptive research design was employed, following Creswell and Plano Clark’s (2017) framework. Data collection methods included questionnaires completed by 28 students, in-depth interviews with 9 students, and relevant documentation analysis. The findings indicate that students generally hold a very positive attitude towards Meta AI, with average scores of 86.19% in the cognitive aspect, 90% in the affective aspect, and 86.92% in the behavioral aspect. The study identified four major benefits of using Meta AI: personalized learning through tailored suggestions and guidance; efficient assessment and immediate feedback that reduce revision time; interactive and immersive learning experiences fostering greater engagement; and improved accessibility by allowing students to use the tool anytime and anywhere via WhatsApp. Despite these advantages, several challenges were also reported, students faced several challenges when using Meta AI, including internet connection issues, generic or context-mismatched suggestions, lack of teacher guidance, and privacy concerns. Based on these findings, the study recommends future research to investigate correlations between AI usage and student academic performance, as well as explore implementation strategies for integrating Meta AI effectively into classroom instruction. These insights contribute to understanding how AI technologies can be harnessed to support EFL writing development while addressing the potential pitfalls associated with their use.